2012
DOI: 10.1039/c2cp23825j
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond to millisecond studies of electron transfer processes in a donor–(π-spacer)–acceptor series of organic dyes for solar cells interacting with titania nanoparticles and ordered nanotube array films

Abstract: Time-resolved emission and absorption spectroscopy are used to study the photoinduced dynamics of forward and back electron transfer processes taking place between a recently synthesized series of donor-(π-spacer)-acceptor organic dyes and semiconductor films. Results are obtained for vertically oriented titania nanotube arrays (inner diameters 36 nm and 70 nm), standard titania nanoparticles (25 nm diameter) and, as a reference, alumina nanoparticle (13 nm diameter) films. The studied dyes contain a triphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 77 publications
(121 reference statements)
3
34
0
Order By: Relevance
“…Recently, we have successfully employed benzothiadiazole benzoic acid (BTBA) as the electron acceptor in combination with two triarylamine cyclopentadithiophene (TAACPDT) electron donors to construct metal-free D-A dyes with an energy gap of about 1.55 eV, exhibiting PCEs of over 11 % under the air mass 1.5 global (AM 1.5G) condition. [26][27][28][29][30] Also, excited-state conformational changes could be intrinsically concomitant with a significant energy loss, as implied by the large Stokes shifts normally recorded for these organic D-A dyes. [21,22] Nowadays, it is still a big challenge for metal-free D-A dyes to catch up with PCEs already attained with organometallic dyes in state-of-the-art DSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have successfully employed benzothiadiazole benzoic acid (BTBA) as the electron acceptor in combination with two triarylamine cyclopentadithiophene (TAACPDT) electron donors to construct metal-free D-A dyes with an energy gap of about 1.55 eV, exhibiting PCEs of over 11 % under the air mass 1.5 global (AM 1.5G) condition. [26][27][28][29][30] Also, excited-state conformational changes could be intrinsically concomitant with a significant energy loss, as implied by the large Stokes shifts normally recorded for these organic D-A dyes. [21,22] Nowadays, it is still a big challenge for metal-free D-A dyes to catch up with PCEs already attained with organometallic dyes in state-of-the-art DSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In artificial photosynthetic systems such as organic polymer solar cells, photons are converted into electrical energy via a series of steps 1117 . First, photons are absorbed by chromophores to generate charge carriers bound by Coulombic interaction (i.e., excitons).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was found that the electron transfer processes have similar dynamics for the NT electrode and the conventional nanoparticle electrode, leading to a similar charge separation efficiency. Therefore, it can be expected that the N-719 dye-sensitized NT electrodes exhibit the typical electron transfer process between the dye molecules and the TiO 2 NT arrays [36]. Here, we focused on the effects of tube length on the photovoltaic properties of the NT electrode.…”
Section: Introductionmentioning
confidence: 99%